205k views
3 votes
PLEASE HELPP! ANYONE??? *cry*

PLEASE HELPP! ANYONE??? *cry*-example-1
User Donkey
by
5.1k points

1 Answer

2 votes

Answer:

10a + 10b / 9x - 9y = 2 / 3

Explanation:

As we can see;

10 * ( a + b ) / 9 * ( x - y ) ⇒ 10a + 10b / 9x - 9y

This concludes that the top part of this equation is multiplied by 10 and the bottom by 9. To derive the solution, let us do the same with 3 / 5;

10a + 10b / 9x - 9y = 3 * 10 / 5 * 9

And simplify, to recieve;

10a + 10b / 9x - 9y = 30 / 45 = 6 / 9 = 2 / 3,

Answer: 10a + 10b / 9x - 9y = 2 / 3

User Tleyden
by
4.4k points